The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1124/dmd.113.052290
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Dependent Inhibition of Organic Anion Transporting Polypeptide 1B1: Comparative Analysis with Prototypical Probe Substrates Estradiol-17β-Glucuronide, Estrone-3-Sulfate, and Sulfobromophthalein

Abstract: Organic anion transporting polypeptide (OATP) 1B1 plays an important role in the hepatic uptake of many drugs, and the evaluation of OATP1B1-mediated drug-drug interactions (DDIs) is emphasized in the latest DDI (draft) guidance documents from U.S. and E.U. regulatory agencies. It has been suggested that some OATP1B1 inhibitors show a discrepancy in their inhibitory potential, depending on the substrates used in the cell-based assay. In this study, inhibitory effects of 14 compounds on the OATP1B1-mediated upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
86
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 37 publications
11
86
1
Order By: Relevance
“…Izumi et al have also recently showed the inhibitory effects of 14 compounds on the OATP1B1-mediated uptake of three kinds of prototypical substrates, E 2 17βG, E-sul and bromosulfophthalein (BSP). 38) As a result, although the K i value of the same inhibitor was sometimes estimated to be very different depending on the substrates tested, regardless of the inhibitors tested, the most potent OATP1B1 inhibition was observed when E 2 17βG was used as a substrate. These results indicated that it is recommended to use the real combination of substrate and inhibitor when predicting the risk of specific DDI cases, while E 2 17βG may be used for a routine high-throughput inhibition assay to perform more conservative DDI prediction.…”
Section: Clinical Importance Of Oatp-mediated Drug-drug Interactionsmentioning
confidence: 99%
“…Izumi et al have also recently showed the inhibitory effects of 14 compounds on the OATP1B1-mediated uptake of three kinds of prototypical substrates, E 2 17βG, E-sul and bromosulfophthalein (BSP). 38) As a result, although the K i value of the same inhibitor was sometimes estimated to be very different depending on the substrates tested, regardless of the inhibitors tested, the most potent OATP1B1 inhibition was observed when E 2 17βG was used as a substrate. These results indicated that it is recommended to use the real combination of substrate and inhibitor when predicting the risk of specific DDI cases, while E 2 17βG may be used for a routine high-throughput inhibition assay to perform more conservative DDI prediction.…”
Section: Clinical Importance Of Oatp-mediated Drug-drug Interactionsmentioning
confidence: 99%
“…The stably OATP1B1-expressing human embryonic kidney 293 (HEK293) cells and the corresponding control HEK293 cells, as established previously (Izumi et al, 2013), were used in this study. The cells were maintained in Dulbecco's modified Eagle medium (Invitrogen, Carlsbad, CA) supplemented with 10% (v/v) of fetal bovine serum, penicillin (final concentration, 100 units/ml), streptomycin (100 mg/ml), and hygromycin B (80 mg/ml) in a humidified incubator containing 5% CO 2 gas at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…One ml of the cell suspension was added to each well of a poly-D-lysine-coated 24-well plate (BD Biosciences, San Jose, CA), and the cells were further cultured in the incubator for 48 hours. The uptake and inhibition studies were performed as described previously elsewhere (Izumi et al, 2013). Briefly, cell culture medium was replaced with prewarmed Krebs Henseleit (KH) buffer (118 mM NaCl, 23.1 mM NaHCO 3 , 4.83 mM KCl, 0.96 mM KH 2 PO 4 , 1.20 mM MgSO 4 , 12.5 mM HEPES, 5.0 mM glucose, and 1.53 mM CaCl 2 , pH 7.4), and the cells were preincubated for 5 minutes at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations